Accounting in networks: A case study of utilization of municipal solid waste incineration bottom ash for road construction material - Korpela, Sanna (My University, 2018)
The purpose of this master thesis is to research a waste-to-energy plant’s municipal solid waste incineration (MSWI) bottom ash and its’ utilization for a road construction material from the perspective of accounting in networks. There are four companies that are involved in this network and their mutual relations are determined. The real process of MSWI bottom ash’s way from a waste-to-energy plant to a road construction site is explained. The utilization of MSWI bottom ash seems to be unprofitable and therefore the opportunity costs of disposal landfilling are calculated. There is a comparison between the costs of circular economic model, that is the utilization of MSWI bottom ash, and the costs of non-circular model, that is the disposal landfilling. And, as the utilization seems to be unprofitable, the purpose of this study is also to explain, are there any costs or revenue that are possible to divide between the companies in the network. The theoretical part consists of earlier researches of networks, accounting in the network, activity-based costing and opportunity costs. The research questions were created from the several earlier researches. This study was carried out with the data received from the case companies. The client company of this study is a waste-to-energy plant whose by-product MSWI bottom ash is. The calculations were made with the activity-based costing model. The analysis is based on the results of the calculations and the information received from the interviews. The results showed that the main burden of the costs of MSWI bottom ash utilization is still in a waste-to-energy plant. But the end user, in this case a road contractor, emphasized that the division of costs is case-specific and all negotiations are individual cases. The opportunity costs of non-circular model showed that even if the costs of MSWI bottom ash utilization are high, the costs of non-circular model are even higher.
Keywords: Circular Economy; Network; Activity-Based Costing; Opportunity costs; MSWI Bottom Ash; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|